179k views
1 vote
Simplify -8+6i/4-2i​

Simplify -8+6i/4-2i​-example-1
User SuperVeetz
by
6.1k points

2 Answers

0 votes

Answer:

−11

5

+

2

5

i

Explanation:

User Mahdi Ghiasi
by
5.5k points
7 votes

Answer:

-1.1+0.4i

Explanation:

Multiply the numerator and the denominator by
4+2i:


(-8+6i)/(4-2i)\cdot (4+2i)/(4+2i)=(-32-16i+24i+12i^2)/(4^2-(2i)^2)\ \ [\text{use formula }a^2-b^2=(a-b)(a+b)]\\ \\=(-32+8i-12)/(16-4i^2)\ \ [\text{remember }i^2=-1]\\ \\=(-44+8i)/(16+4)\\ \\=(-44+8i)/(20)\\ \\=-(11)/(10)+(4)/(10)i\\ \\=-1.1+0.4i

User Danny Elliott
by
5.4k points